Identification of Loci and Candidate Genes Analyses for Tocopherol Concentration of Soybean Seed - Sui, Meinan; Jing, Yan; Li, Haiyan; Zhan, Yuhang; Luo, Jian; Teng, Weili; Qiu, Lijuan; Zheng, Hongkun; Li, Wenbin; Zhao, Xue; Han, Yingpeng (Frontiers in Plant Science, 2020)
Tocopherol (Toc) occurs in soybean seeds and is extracted together with the soybean oil. Toc is utilized as an antioxidant in food and an additive in animal feed. A total of 180 representative accessions and 144 recombinant inbred lines (RILs) from the cross of ‘Hefeng 25’ and ‘OAC Bayfield’ were selected to evaluate individuals and total Toc concentrations in soybean seeds. The 180 soybean samples were sequenced by the approach of Specific Locus Amplified Fragment Sequencing (SLAF-seq). A total of 22,611 single nucleotide polymorphisms (SNPs) were developed. Nineteen quantitative trait nucleotides (QTNs) were identified associated with individual or total-Toc based on genome-wide association analysis (GWAS). Among them, three QTNs located near known QTLs, and 16 were novel. Eighteen QTLs and nine eQTLs were also detected by linkage mapping. The QTN rs9337368 on Chr.02 was co-localized according to the linkage mapping of the RILs and genome-wide association analysis, and regarded as a stable locus for mining the candidate genes in association with Toc. A total of 42 candidate genes near the 200 kbp flanking region of this identified locus were found. Upon a gene-based association, 11 SNPs from 5 genes out of the 42 candidates were detected. Expression levels analysis of 5 candidate genes revealed that two genes were significantly related to Toc content. The identified loci, along with the candidate genes, might be valuable for increasing the Toc concentration in soybean seeds and improving the nutritional value of soybean oil.